Perfil de idosos em acompanhamento ambulatorial e preditores de quedas - Gomes, Grace Angélica de Oliveira [UNESP]; Cintra, Fernanda Aparecida; Batista, Fernanda Sotelo; Neri, Anita Liberalesso; Guariento, Maria Elena; Sousa, Maria da Luz Rosario de; D'Elboux, Maria José (FapUNIFESP (SciELO), 2013)
Context and Objectives: Falls are a serious public health problem and are one of the biggest reasons for hospitalization, morbidity and mortality among elderly people. Moreover, few studies on predictors of falls have been conducted in low and middle income countries. The aim here was to identify elderly outpatient profiles according to sociodemographic, clinical, physical and functional variables and correlate them with occurrences of falls among these subjects. Design and Setting: Cross-sectional descriptive study forming part of the project Quality of Life of Frail Elderly People, carried out in Campinas, Brazil. Methods: The subjects were 145 elderly individuals (76.3 ± 7.8 years old), of whom 65% were women, who were living in the city of Campinas or nearby and were attended at the geriatric outpatient clinic of a University Hospital. Sociodemographic, clinical, physical and functional data, as well as fall occurrence data, were gathered. Cluster analyses and comparisons between groups were carried out. Results: Cluster analysis identified two distinct groups related to the study variables, and the determinants for this distinction were: gender, marital status, physical performance, handgrip strength and functional independence. These groups were compared according to occurrences of falls over the last year, and significant differences between them were found. Conclusions: The results showed that greater occurrences of falls were associated with a profile of elderly people comprising female gender, single status, lower muscle strength and physical performance regarding balance and gait, and lower independence in motor tasks for activities of daily living.
Elderly outpatient profile and predictors of falls
Keywords: Activities of daily living; Aging; Gait; Muscle strength; Postural balance; aged; Brazil; cluster analysis; cross-sectional study; demography; falling; female; gender; grip strength; human; independence; major clinical study; male; marriage; outpatient; outpatient department; patient information; physical performance; social aspect; university hospital